Small Synagogue: Great Strides - Tomal, Maureen (My University, 2009)
In 1972, the Chippewa Valley Lodge of B'nai B'rith sparked national attention when members voted to remove the "male only" clause in B'nai B'rith membership. Breaking a long tradition of male fraternity, the lodge added two females to their roster, angering other B'nai B'rith Lodges and the B'nai B'rith national headquarters. Despite heated exchange from the district Grand Lodges and national B'nai B'rith leaders, the Chippewa Valley Lodge continued to allow women to serve as full members within their Lodge. Refusing to stop there, the Lodge fought back vehemently against what they considered to be a discriminatory policy and petitioned the leadership to have gender removed from membership requirements. Ultimately their efforts led to a national vote that decentralized the establishment of membership requirements, enabling individual branches to decide on the issue of gender and membership. This victory, while a product of the Chippewa Valley Lodge's leadership, fits within the context of the events that occurred within the civil rights movement, second wave feminism, and Conservative Judaism.
Keywords: B'nai B'rith--History; B'nai B'rith. Lodge 1474 (Chippewa River Valley, Wis.); Women's rights--Wisconsin--Chippeway River Valley; Women's rights--United States--History; Judaism--Wisconsin--Chippewa River Valley--History; Women in Judaism--Wisconsin--Chippewa River Valley; Women in Judaism--History